The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/npp.2015.226
|View full text |Cite
|
Sign up to set email alerts
|

Relative Timing Between Kappa Opioid Receptor Activation and Cocaine Determines the Impact on Reward and Dopamine Release

Abstract: Negative affective states can increase the rewarding value of drugs of abuse and promote drug taking. Chronic cocaine exposure increases levels of the neuropeptide dynorphin, an endogenous ligand at kappa opioid receptors (KOR) that suppresses dopamine release in the nucleus accumbens (NAc) and elicits negative affective states upon drug withdrawal. However, there is evidence that the effects of KOR activation on affective state are biphasic: immediate aversive effects are followed by delayed increases in rewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 67 publications
(98 reference statements)
2
56
0
Order By: Relevance
“…The dynorphin/KOR system is involved in mediating negative affective states (Bruchas et al, 2010; Berger et al, 2013). For example, elevations in intracranial self-stimulation thresholds, which model anhedonia, are found after prolonged activation of KORs (Chartoff et al, 2015). The current data and previous studies have shown that excessive exposure to drugs of abuse results in an upregulated dynorphin/KOR system (Lindholm et al, 2000; Kissler et al, 2014; Rose et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The dynorphin/KOR system is involved in mediating negative affective states (Bruchas et al, 2010; Berger et al, 2013). For example, elevations in intracranial self-stimulation thresholds, which model anhedonia, are found after prolonged activation of KORs (Chartoff et al, 2015). The current data and previous studies have shown that excessive exposure to drugs of abuse results in an upregulated dynorphin/KOR system (Lindholm et al, 2000; Kissler et al, 2014; Rose et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study showed that the KOR agonist, U50,488, attenuated, rather than increased, ethanol intake in Lewis rats (Lindholm et al, 2001). However, KOR activation time-dependently modulates vulnerability to drugs of abuse and reward processing; for example, a recent study showed that administration of cocaine 15 min after KOR activation with salvinorin A (salA; the time point used in Lindholm et al, 2001) decreased ICSS thresholds and increased DA release, consistent with increased positive affect, while cocaine administration 24 h after KOR activation increased ICSS thresholds and decreased DA release, indicating a negative affective state (Chartoff et al, 2016). Finally, another study showed that nor-BNI increased ethanol intake in rats that were housed in a manner similar to GH animals in the current study (Mitchell et al, 2005).…”
Section: Si-induced Potentiation Of Kor System Responsivenessmentioning
confidence: 99%
“…Previous data suggest that exposure to chronic stress, such as repeated withdrawal from chronic intermittent ethanol (CIE) exposure, leads to prolonged activation of KORs (Walker and Koob, 2008), possibly contributing to reduced DA function, which is positively correlated with negative affect (see Koob et al, 2014 for a review). Elevations in intra-cranial self-stimulation (ICSS) thresholds are associated with anhedonia, and a recent study showed that prolonged activation of KORs resulted in significantly elevated ICSS thresholds (Chartoff et al, 2016). Notably, negative affective states such as anhedonia facilitate motivation to increase the intake of drugs (Baarendse et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Blocking KOR, however, inhibits stress-induced escalations in cocaine self-administration, alcohol intake, and preference for nicotine (Redila and Chavkin, 2008; Sperling et al, 2010). Prolonged activation of KORs causes a significant elevation in ICSS thresholds, a behavior indicative of anhedonia (Chartoff et al, 2016). It is this anhedonia and negative affective state that motivates increased drug taking (Baarendse and Vanderschuren, 2012).…”
Section: Dopamine and Kappa Opioid System In Chronic Pain And Stress mentioning
confidence: 99%